2011
DOI: 10.1111/j.1749-4486.2011.02387.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study evaluating spontaneous healing of aetiology, size and type‐different groups of traumatic tympanic membrane perforation

Abstract: The clinical outcome of spontaneous healing of acute tympanic membrane perforations is generally associated with perforation size, aetiology and whether dry or with a serosanguenous discharge. The sequence of granulation tissue formation and epithelial migration differs during the healing of traumatic tympanic membrane formation in serosanguinous discharge conditions and dry perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 25 publications
8
68
0
6
Order By: Relevance
“…The spontaneous closure rates and closure times in the present study are in accordance with results from other studies. [1][2][3]5 Several factors might be important determinants of closure time, such as age, ear discharge and perforation size. With multivariate analysis, we found that perforation size was the single determining factor related to closure time, a finding also reported in some other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spontaneous closure rates and closure times in the present study are in accordance with results from other studies. [1][2][3]5 Several factors might be important determinants of closure time, such as age, ear discharge and perforation size. With multivariate analysis, we found that perforation size was the single determining factor related to closure time, a finding also reported in some other studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 Subsequent studies showed similar findings, with spontaneous closure rates ranging from 80 to 97 per cent. [2][3][4][5] For cases of large perforations and blast injuries, spontaneous closure rates have been observed to range from 56 to 82 per cent. 6,7 Studies comparing outcomes after observation only versus different active surgical interventions using various techniques have shown spontaneous closure rates between 53 and 86 per cent in the observation only groups, 8 and closure rates between 88 and 100 per cent in the operated groups.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Similarly, the results from a study investigating a large sample of spontaneously healing traumatic TMPs showed that preexisting sclerotic plaques were the primary cause of nonhealing. 9 The there was no detailed description of management of the perforated edge: For the experimental group, the authors stated, ''The perforated edges were scarified, and then a bacterial cellulose membrane was placed over the perforation laterally to the tympanic remains. The membrane was held in place by self-adhesion.''…”
Section: Dear Editormentioning
confidence: 99%
“…We realize that the silk patch enhanced water absorption, and by immersing it in saline a moist environment could be created. Previous studies have shown that moist environments are able to accelerate tympanic membrane healing and reduce closure time [6,7]. Amadasun [8] reported a closure rate of 92.3% in 13 of 15 traumatic TMP patients (86.7%) using a semisolid gentamicin ointment plug (Gentalek, Lek Pharmaceutical and Chemical Company, Veroskova, Slovenia with NAFDAC no.…”
mentioning
confidence: 99%